Interconnection of linguistics and musical art: Specifics of music semantics development - Solomonova, Olga B.; Zavgorodnia, Galyna F.; Muravska, Olha V.; Chernoivanenko, Alla D.; Aleksandrova, Oksana O. (Linguistics and Culture Review, 2021)
The terminology of music semiology, which is an academic discipline with a significant educational resonance and a necessary component of music and educational practice at its higher educational and qualification levels, lies at the intersection of the main aspects of musicology such as the history of music, the theory and analysis of musical forms, music aesthetics and the theory of music interpretation, and others. Music semiology covers the transitional methodological abilities due to its subject reference points and the wide range of the material involved in the cognitive field. Music semiology can be considered a necessary basic discipline for the professional training of musicologists and practicing musicians of any programme. There is no doubt about the importance of mastering the language system, which is fundamental in the chosen field of communication. As an academic discipline, music semiology can be presented according to the way its terminology is built, it includes three main themes among which each of the following continues the meaning of the previous one by deepening and enlarging, detailing in an analytical way. Scientific novelty is determined by the fact that unlike music semiotics and the theory of music semantics.